Prevalencia de Ehrlichiasis canina en el Período 2010-2020, en el Cantón Guayaquil - Franco Guzñay, Johanna Patricia (2021)
Documentary research was carried out with the aim of generating information on the prevalence of canine Ehrlichiosis and its susceptibility in the age, sex and race variables in the Canton Guayaquil in the last 10 years. The research was of bibliographic documentary type by the deductive inductive method, it was elaborated according to the collection and review of scientific articles and books published on the web, in topics related to the detection of the presence of Ehrlichia canis in different laboratory diagnostic methods. Information was collected between February and March 2021. This bibliographic research showed the prevalence of this disease in the different ages of the animals, as well as its sex and breed, demonstrating that the animals with the greatest susceptibility are adult dogs over 5 years, males and half-breeds, also the little knowledge that pet owners have about the disease in sectors where there is no control in stray dogs, the absence of health plans to avoid the increases of positive cases of said pathology in seasons. In general, the purpose is to achieve the reduction of this disease through greater awareness and dissemination of information that generate knowledge about hemoparsites and their consequences in both animals and humans in the population, the public health problems they generate and how veterinarians face these diseases both in the different methods of diagnosis and treatments that are adjusted to the want and power of the owners of the animals. Keywords: Canine Ehrlichiosis – blood- dog - susceptibility